Dominant TET2 mutations predict adverse prognosis in cytogenetically normal acute myeloid leukemia patients - Hao, Zhuanghui; Xia, Jingjing; Bian, Sicheng; Song, Miaoke; Zhang, Miao; Feng, Jingyi; Li, Shuo; Wang, Huichao; Zhang, Yaofang; Yang, Wanfang; Chang, Jianmei; Ren, Fanggang; et al. (Frontiers in Oncology, 2026)
ObjectiveThis study aimed to characterize TET2 mutations in CN-AML, assess their clinical features, and evaluate the prognostic impact of VAF and clonal hierarchy on overall survival (OS) and relapse-free survival (RFS).MethodsA cohort of 206 adult CN-AML patients was analyzed for the presence of TET2 mutation characteristics, variant allele frequency (VAF) and clonal status. Clinical and prognostic implications were evaluated through survival analyses and validated by the Beat AML public database.ResultsTET2 mutations were detected in 18.9% of CN-AML patients, with a median age of 55 years, significantly older than TET2 wild-type patients (P < 0.001). OS and RFS were no difference in the high-VAF group and low-VAF group. Patients with dominant TET2 mutations exhibited significantly shorter OS and RFS compared to subclonal group (P < 0.05). Multivariate Cox regression identified dominant TET2 mutations as an independent adverse prognostic factor for OS (HR = 2.026,P = 0.039). A nomogram model based on these findings demonstrated robust predictive performance (AUC = 0.735) and was validated by the Beat AML database.ConclusionsThe prognostic impact of TET2 mutations is not determined by VAF, but rather by TET2 clonal dominance and the interplay between mutations within the same clone.